Penetapan Kadar Flavonoid Ekstrak dan Fraksi Kulit Buah Citrus reticulata - Siska Musiam; Erna Prihandiwati; Eka Kumalasari; Aisyah Aisyah (Jurnal Farmasi Indonesia, 2022)
Citrus reticulata is one of the varieties of citrus endemic to South Kalimantan. So far, the people of South Kalimantan have only used the pulp of the citrus fruit, while the skin is disposed of as waste. Therefore, this study was conducted to see the value of the benefits of the Citrus reticulata rind waste by testing the levels of flavonoids from the extract and its fractions. The rind extraction of Citrus reticulata was carried out by maceration method using methanol as a solvent. The extract obtained was then fractionated using the liquid-liquid method using n-hexane, chloroform, ethyl acetate, and water as solvents. The extract and each fraction were determined for the level of flavonoids using a UV-Visible spectrophotometer at a wavelength of 413 nm and a series of standard concentrations of quercetin 35; 50; 65; 80; and 95 ppm. The results showed that the levels of flavonoids from the highest to the lowest were in the water fraction, methanol extract, n-hexane fraction, ethyl acetate fraction, and chloroform fraction with the respective values ​​of 53.635 ± 0.00697; 30.083 ± 0.00386; 15,524 ± 0.00423; 9.787 ± 0.00198%(w/w).